Heavy-light mesons scattering from nucleons: Quark-gluon and meson exchanges - Fontoura, C. E. [UNESP] (AIP Publishing, 2010)
We investigate the scattering of heavy-light K and D mesons by nucleons at low energies. The short-distance part of the interaction is described by quark-gluon interchange and the longdistance part is described by a one-meson-exchange model that includes the contributions of vector (ρ, ω) and scalar (σ) mesons. The microscopic quark model incorporates a confining Coulomb potential extracted from lattice QCD simulations and a transverse hyperfine interaction consistent with a finite gluon propagator in the infrared. The derived effective meson-nucleon potential is used in a Lippmann-Schwinger equation to obtain s-wave phase shifts. Our final aim is to set up a theoretical framework that can be extended to finite temperatures and baryon densities. © 2010 American Institute of Physics.
Keywords: Chiral symmetry; heavy-light mesons; meson-baryon interactions; Quantum chromodynamics; Quark models